A Comparative Study of Oral Microbiota in Infants with Complete Cleft Lip and Palate or Cleft Soft Palate. (14th March 2017) - Machorowska-Pieniążek, Agnieszka; Mertas, Anna; Skucha-Nowak, Małgorzata; Tanasiewicz, Marta; Morawiec, Tadeusz
Abstract : Few reports have been published on the early microbiota in infants with various types of cleft palate. We assessed the formation of the oral microbiota in infants with complete cleft lip and palate (CLP n = 30 ) or cleft soft palate (CSP n = 25 ) in the neonatal period (T1 time) and again in the gum pad stage (T2 time). Culture swabs from the tongue, palate, and/or cleft margin at T1 and T2 were taken. We analysed the prevalence of the given bacterial species (the percentage) and the proportions in which the palate and tongue were colonised by each microorganism. At T1, Streptococcus mitis (S. mitis) were the most frequently detected in subjects with CLP or CSP (63% and 60%, resp.). A significantly higher frequency of methicillin-sensitive Staphylococcus aureus ( S. aureus MSSA) was observed in CLP compared to the CSP group. At T2, significantly higher percentages of S. mitis, S. aureus MSSA, Staphylococcus epidermidis, and members of the Enterobacteriaceae family were noted in CLP infants compared to the CSP. S. mitis and Streptococcus sanguinis appeared with the greatest frequency on the tongue, whereas Streptococcus salivarius was predominant on the palate. The development of the microbiota in CLP subjects was characterised by a significant increase in the prevalence of pathogenic bacteria.